Migration and Urbanisation in Post-Apartheid South Africa - Jan David Bakker; Christopher Parsons; Ferdinand Rauch (Institute for the Study of Labor (IZA), 2016)
Under apartheid, black South Africans were severely restricted in their choice of location and many were forced to live in homelands. Following the abolition of apartheid they were free to migrate. Given gravity, a town nearer to the homelands can be expected to receive a larger inflow of people than a more distant town following the removal of mobility restrictions. Exploting this exogenous variation, we study the effect of migration on urbanisation and the distribution of population. In particular, we test if migration inflows led to displacement, path dependence, or agglomeration in destination areas. We find evidence for path dependence in the aggregate, but substantial heterogeneity across town densities. An exogenous population shock leads to an increase of the urban relative to the rural population, which suggests that exogenous migration shocks can foster urbanisation in the medium run.
Keywords: R12; R23; N97; O18; 330; economic geography; migration; urbanisation; natural experiment